Electrochemical studies of tris(cyclopentadienyl)thorium and uranium complexes in the +2, +3, and +4 oxidation states - Wedal, Justin C. (Chem Sci, 2021)
Electrochemical measurements on tris(cyclopentadienyl)thorium and uranium compounds in the +2, +3, and +4 oxidation states are reported with C(5)H(3)(SiMe(3))(2), C(5)H(4)SiMe(3), and C(5)Me(4)H ligands. The reduction potentials for both U and Th complexes trend with the electron donating abilities of the cyclopentadienyl ligand. Thorium complexes have more negative An(iii)/An(ii) reduction potentials than the uranium analogs. Electrochemical measurements of isolated Th(ii) complexes indicated that the Th(iii)/Th(ii) couple was surprisingly similar to the Th(iv)/Th(iii) couple in Cp′′-ligated complexes. This suggested that Th(ii) complexes could be prepared from Th(iv) precursors and this was demonstrated synthetically by isolation of [Image: see text] directly from [Image: see text] UV-visible spectroelectrochemical measurements and reactions of [Image: see text] with elemental barium indicated that the thorium system undergoes sequential one electron transformations.